PERBANDINGAN HASIL BELAJAR MENGGUNAKAN MODEL ST DAN TS DENGAN MEMPERHATIKAN MOTIVASI BERPRESTASI - Eka Yulistiana; Edy Purnomo; Tedi Rusman (FKIP Unila, 2014)
This study examines the differences between the model and the effectiveness of snowball throwing (ST) learning model and talking stick (TS) with attention to achievement motivation in the achievement of learning outcomes Integrated Social Science. The method in this study is the method of quasi-experimental research design with treatment by level. Research instruments are using test instruments and questionnaires. Hypothesis testing using a two-way analysis of variance formula and t-test of two independent samples. Findings of this study were (1) there is a difference between snowball throwing achievement and talking stick model, (2) talking stick learning model is higher than snowball throwing viewed from a high performance motivation, (3) talking stick learning model higher than snowball throwing model seen from the low performance motivation, (4) there is no interaction between the model of learning with performance motivation on students achievement.Penelitian ini mengkaji perbedaan dan keefektifan antara model pembelajaran snowball throwing (ST) dan talking stick (TS) dengan memperhatikan motivasi berprestasi dalam pencapaian hasil belajar IPS Terpadu. Metode dalam penelitian ini adalah metode eksperimen semu dengan desain penelitian treatment by level. Instrumen penelitian menggunakan tes dan angket. Pengujian hipotesis menggunakan rumus analisis varian dua jalan dan t-test dua sampel independen. Temuan penelitian ini adalah (1) Ada perbedaan hasil belajar antara model pembelajaran Snowball Throwing dan Talking Stick, (2) Model pembelajaran Talking Stick lebih tinggi daripada Snowball Throwing dilihat dari motivasi berprestasi tinggi, (3) Model pembelajaran Talking Stick rendah daripada Snowball Throwing dilihat dari motivasi berprestasi rendah, (4) Tidak ada interaksi antara model pembelajaran dengan motivasi berprestasi terhadap hasil belajar siswa.Kata kunci: hasil belajar, motivasi, ST, TS